2016
DOI: 10.1080/15298868.2016.1206033
|View full text |Cite
|
Sign up to set email alerts
|

The role of mortality awareness in hero identification

Abstract: Three studies examine hypotheses derived from terror management theory to investigate the relationship between mortality concerns and hero identification. Study 1 found reminders of death, followed by a distraction task and a self-prime, led to greater inclusion of heroes in the self. Study 2 found that writing about a personal hero, but not other's heroes or acquaintances, led to lower death-thought accessibility after being reminded of mortality. Finally, Study 3 found that after death reminders, participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Third, the finding that thinking about heroes can increase perceptions of personal power and that this is evident when consumers experience psychological threats makes a further novel contribution to the literature. This study supports previous research showing that heroes influence others psychologically, particularly during times of threat (e.g., Allison & Goethals, 2011;Kinsella, Ritchie, & Igou, 2015b;Sullivan & Venter, 2005); however, this finding also adds to existing scholarship on heroes and psychological threat (Green, Van Tongeren, Cairo, & Hagiwara, 2017;McCabe, Carpenter, & Arndt, 2016) by specifying a specific mediating variable: personal power.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Third, the finding that thinking about heroes can increase perceptions of personal power and that this is evident when consumers experience psychological threats makes a further novel contribution to the literature. This study supports previous research showing that heroes influence others psychologically, particularly during times of threat (e.g., Allison & Goethals, 2011;Kinsella, Ritchie, & Igou, 2015b;Sullivan & Venter, 2005); however, this finding also adds to existing scholarship on heroes and psychological threat (Green, Van Tongeren, Cairo, & Hagiwara, 2017;McCabe, Carpenter, & Arndt, 2016) by specifying a specific mediating variable: personal power.…”
Section: Introductionsupporting
confidence: 89%
“…Next, participants were randomly assigned to either hero or nohero reminder conditions (McCabe et al, 2016). As in Study 2a,…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…In a subsequent study of British university students, Routledge and Arndt (2008) found that participants who were asked to think about their death expressed more readiness to make self-sacrifices for their country (e.g., “I would die for England”) than participants who were asked to think about other negative states such as dental pain. In addition, indirect evidence was found in two recent studies of heroism: As compared with a control condition, mortality salience led participants to report less pain on a cold pressor task when pain tolerance was linked to heroism (McCabe, Carpenter, & Arndt, 2015) and to heightened identification with heroes who sacrificed their lives for a cause (McCabe, Carpenter, & Arndt, 2016).…”
Section: Terror Management Mechanisms: Self-sacrifice As a Death-anxi...mentioning
confidence: 99%
“…In the present set of studies, no values or social norms were made explicitly salient, clearly limiting our conclusions. Other moderators could also warrant consideration, for example, personal connection to the hero (McCabe et al, 2016), perceived similarity to the hero and accessibility of the heroes' achievements (Lockwood & Kunda, 1997), ingroup salience, and differences in the cultural worship of heroes in general. In all studies, to assess heroic perceptions we used items that had been chosen due to their face validity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, McCabe, Carpenter, and Arndt (2016) found that after MS and a selffocus prime, greater inclusion of a recalled hero in the self was found. Additionally, death-thought accessibility after MS was reduced when participants were offered the possibility to write about a personal hero or identify with a hero.…”
Section: Research On Heroes In Terror Management Theorymentioning
confidence: 98%